Assessment of the health of a river ecosystem due to the impact of pollution from industrial discharge using instrumental neutron activation analysis and inductively coupled plasma-mass spectrometry - Mohd Yusof, Alias; Thanapalasingham, V.; Wood, A. K. H. (Akadémiai Kiadó, 2007)

(untitled)
Abstract Inductively coupled plasma-mass spectrometry (ICP-MS) and neutron activation analysis (NAA) were employed in the determination of heavy metal concentrations in water, plant and sediment samples to assess the extent of heavy metal pollution in a river system which is located within an industrial zone. Elemental concentrations of As, Pb, Hg, Cr, Cu, Cd, Ni and Zn were measured in the samples. Statistical analysis was performed on the data obtained to look for trends in the pollution pattern of these elements on the river system. The trend in concentrations of heavy metals pollution in water samples is in the order of Zn > Cu > Ni > Cr > As > Pb > Hg > Cd, whereas in plants the order is Zn > Cr > Cu > Pb > Ni > As > Hg > Cd and in sediments Zn > Cu > Pb > Ni > As > Hg.